Otoritas Fatwa di Indonesia: Variasi Respons Pengguna Twitter terhadap Fatwa MUI tentang Haram Golput pada Pemilu - Fatihunnada, Fatihunnada; Umniati, Iffatul; Raspiani, Raspiani (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2021)
The fatwas of Majlis Ulama Indonesia often incite controversy among Indonesian Muslims. This includes a fatwa on the prohibition of golongan putih (golput; non-voting behavior) that was issued in 2009. This fatwa sparkes heated debates among netizens, inluding Twitter users during the 2014 and 2019 presidential elections. This data required for this research were collected from the Twitter in the form of tweets in several months in 2014 using the python module, namely the twitter scraper which was then stored in the form of Comma Separated Values (CSV). Out of 2,491 tweets, 1,142 tweets or 45.84% contain neutral responses, 1,071 tweert or 42.95% contain negative responses, and 278 tweets or 11.16 % contain positive responses. This figure shows that the rejection of the fatwa on the prohibition of golput was greater than its acceptance by netizens. More importantly, this indicate that the authority of MUI in issuing fatwas is not fully accepted and obeyed by Indonesian Muslims.